Masculinity in Muslim media: a case study of Radio Islam - Dadi Patel, Aaisha (My University, 2018)
This project examines the ways in which Radio Islam, a South African community radio station, constructs masculinity in the South African Indian Muslim community. This community is its largest audience. The radio station is strongly influenced by the ideologies and rulings of the Jamiatul Ulama, an ideological body whose teachings stem from Indo-Pak interpretations of Islam and with whom much of the South African Indian Muslim community align themselves. The conflation of this culture and religion in this context results in patriarchal and misogynistic teachings being repeated by this body without much questioning, resulting in the common upliftment of men and confinement of women in the community to certain roles and spaces only. Through the examination and discourse analysis of broadcasted content on Radio Islam in three categories that have many gendered dynamics to them - hijab, marriage, and Ramadan - this study aims to unpack the way in which masculinity is constructed, and the extents to which these constructions then facilitate the entrenchment of patriarchy in the broader South African Muslim community.
A dissertation submitted in full fulfilment of the requirements for the degree of Master of Arts by Research in Media Studies, Department of Media Studies, Faculty of Humanities, University of the Witwatersrand, February 2018
Keywords: Radio Islam; Community radio--South Africa; Radio broadcasting--South Africa; Masculinity--South Africa